Thermomechanical effect in molecular crystals: the role of halogen-bonding interactions - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nanubolu, Jagadeesh Babu; Nangia, Ashwini (IUCRJ, 2017)
The design and synthesis of mechanically responsive materials is interesting because they are potential candidates to convert thermal energy into mechanical work. Reported in this paper are thermosalient effects in a series of halogen derivatives of salinazids. The chloro derivative, with higher electronegativity and a weaker inter-halogen bond strength (Cl center dot center dot center dot Cl) exhibits an excellent thermal response, whereas the response is weaker in the iodo derivative with stronger I center dot center dot center dot I halogen bonding. 3,5-Dichlorosalinazid (Compound-A) exists in three polymorphic forms, two room-temperature polymorphs (Forms I and II) and one high-temperature modification (Form III). The transformation of Form I to Form III upon heating at 328-333 K is a reversible thermosalient transition, whereas the transformation of Form II to Form III is irreversible and nonthermosalient. 3,5-Dibromo- (Compound-B) and 3-bromo-5-chloro(Compound-C) salinazid are both dimorphic: the Form I to Form II transition in Compound-B is irreversible, whereas Compound-C shows a reversible thermosalient effect (362-365 K). In the case of 3,5-diiodosalinazid (CompoundD) and 3,5-difluorosalinazid (Compound-E), no phase transitions or thermal effects were observed. The thermosalient behaviour of these halosalinazid molecular crystals is understood from the anisotropy in the cell parameters (an increase in the a axis and a decrease in the b and c axes upon heating) and the sudden release of accumulated strain during the phase transition. The dihalogen salinazid derivatives (chlorine to iodine) show a decrease in thermal effects with an increase in halogen-bond strength. Interestingly, Compound-B shows solid-state photochromism in its polymorphs along with the thermosalient effect, wherein Form I is cyan and Form II is light orange.

Enantioselective Cu(I)-catalyzed borylative cyclization of enone-tethered cyclohexadienones and mechanistic insights - Jadhav, Sandip B.; Dash, Soumya Ranjan; Maurya, Sundaram; Nanubolu, Jagadeesh Babu; Vanka, Kumar; Chegondi, Rambabu (Nature Communications, 2022)
Rapidly building molecular structures with both elements of complexity and flexibility is a key goal of organic synthesis. Here the authors show a tandem copper-catalyzed beta-borylation/Michael addition on prochiral enone-tethered 2,5-cyclohexadienones, to generate bicyclic borylated products in high yield and enantioselectivity. The catalytic asymmetric borylation of conjugated carbonyls followed by stereoselective intramolecular cascade cyclizations with in situ generated chiral enolates are extremely rare. Herein, we report the enantioselective Cu(I)-catalyzed beta-borylation/Michael addition on prochiral enone-tethered 2,5-cyclohexadienones. This asymmetric desymmetrization strategy has a broad range of substrate scope to generate densely functionalized bicyclic enones bearing four contiguous stereocenters with excellent yield, enantioselectivity, and diastereoselectivity. One-pot borylation/cyclization/oxidation via the sequential addition of sodium perborate reagent affords the corresponding alcohols without affecting yield and enantioselectivity. The synthetic potential of this reaction is explored through gram-scale reactions and further chemoselective transformations on products. DFT calculations explain the requirement of the base in an equimolar ratio in the reaction, as it leads to the formation of a lithium-enolate complex to undergo C-C bond formation via a chair-like transition state, with a barrier that is 22.5 kcal/mol more favourable than that of the copper-enolate complex.